Oil/water separation techniques: a review of recent progresses and future directions. Issue 31 (17th May 2017) - Gupta, Raju Kumar; Dunderdale, Gary J.; England, Matt W.; Hozumi, Atsushi
Abstract : The recent progress of oil/water separation technologies using various materials that possess surface superwetting properties is summarized. Abstract : Oil/water separation is a field of high significance as it has direct practical implications for resolving the problem of industrial oily wastewater and other oil/water pollution. Therefore, the development of functional materials for efficient treatment of oil-polluted water is imperative. In this feature article, we have reviewed the recent progress of oil/water separation technologies based on filtration and absorption methods using various materials that possess surface superwetting properties. In each section, we present in detail representative work and describe the concepts, employed materials, fabrication methods, and the effects of their wetting/dewetting behaviors on oil/water separation. Finally, the challenges and future research directions of this promising research field are briefly discussed.